European misunderstanding - Gauron, André (Algora Pub., 2000)
An advisor to Lionel Jospin, this author paints a picture of the messy march toward a unified Europe and calls for a more representative system, starting with a Constitution for al or Europe.
Keywords: European Union.; Europe -- Economic integration.; Europe -- Intégration économique.; BUSINESS & ECONOMICS -- International -- General.; BUSINESS & ECONOMICS -- International -- Economics.; International economic integration; Europe